Improving Students' Reading Comprehension Through Project Based Learning - Hujaemah, Emah; Tarihoran, Naf’an; Amalia, Ila (CV. Kayaswara, 2025)
This study aims to improving student's reading comprehension through project based learning a collaborative classroom action research at the third grade of MTs Sirajul Afidah Serang Banten. This type of research is a collaborative Classroom Action Research (CAR). The model in this research use Kemmis and Mc Taggart model. The subjects of this study were third grade students of MTs Sirajul Afidah Banten Serang consisting of 10 male students and 20 female students. The data collection technique in this study uses tests, and observations. Qualitative data collection instruments use observation sheets and quantitatively use reading comprehension tests. Data analysis technique used is quantitative and qualitative data descriptive analysis. This study shows that the use of method project based learnig and flip chart media project can improve reading comprehension on narrative text of eighth grade students of MTs Sirojul Afidah-Gunungsari. Improved reading comprehension is evidenced by the grade point average of 61.3 rising to 77.7 and 85.8. The percentage of achievement of the average score of reading skill has increased on pre-action 36%, in cycle I 66%, and in cycle II is 93%. The result of reading comprehension test after the implementation of learning comprehension reading by method project based learning flip chart media project continue to increase and show effectiveness in learning to improve reading comprehension ability in students of Class IX B MTs Sirojul Afidah Gunungsari. The increase is implied by the success indicators of the process and the product in each cycle.